Effects of pride-tagged money and surprise-tagged money on online tipping. Issue 3 (25th November 2020) - Yang, Pianpian; Zhang, Qingyu; Feng, Yuanyue
Abstract : Purpose: With the rise of social media, online tipping has developed markedly in recent years. Drawing on emotional accounting, this research examined the effects of pride-tagged money (PTM) and surprise-tagged money (STM) on online tipping. It examined the mediating role of self-inflation and the moderating role of the perceived importance of money in the proposed relationship. Design/methodology/approach: Five experimental studies were conducted to test the hypotheses using ANOVA, SmartPLS3 and bootstrap analyses. Findings: The results reveal that pride-tagged (vs surprise-tagged) money leads to higher self-inflation, which leads to an increased willingness to engage in online tipping. It illustrates that when the perceived importance of money is low, PTM results in a higher willingness to engage in online tipping than STM. However, when the perceived importance of money is high, the effect of PTM (vs STM) on the willingness to conduct online tipping is attenuated, and no significant difference exists in the willingness to engage in online tipping between people with PTM and those with STM. In addition, it shows that PTM (vs STM) leads to a higher amount of online tipping, and self-inflation mediates the proposed relationship. Practical implications: Practically, web-based marketing managers should design programs (e.g. content that encourages users to feel pride in their achievements) that cause users to emotionally tag their money with pride as a means of increasing their willingness to engage in online tipping and to increase the amount of such tipping. Originality/value: To the best of the authors' knowledge, this study provides the first evidence of how different sources of money influence online tipping.